Effect of calf-starter protein solubility on calf performance - J.L. Morrill; P.G. Reddy; Keith C. Behnke; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1985)
Three starters containing differently processed protein supplements were fed to Holstein heifer calves, using an early weaning program. One starter contained soybean meal. The other starters contained soybean grits processed through an extrusion cooker to reduce the protein solubility to an intermediate (PDI>50%) or low (PDI<15 %) level. Calf performance was similar on all three starters.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Dairy Day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Protein; Calf performance; Soybean meal; Microbial protein